The Political Economy of Pricing Car Access to Downtown Commercial Districts - Bruno De Borger; Antonio Russo (Center for Economic Studies and ifo Institute (CESifo), 2015)
We develop a positive theory of pricing car access (by parking fees or cordon tolls) to downtown commercial districts. The model accounts for the special interests of downtown retailers and competing superstores at the edge of the city, and studies how lobbying by both groups shapes the government's policy. We find that downtown retailers typically have steeper lobbying contribution schedules than superstores, which induces the government to underprice central roads and parking spaces. This result is strengthened if some consumers visit both downtown and edge-of-town retailers. The presence of an alternative travel mode (e.g. public transport) does not weaken downtown retailers' incentives to oppose car tariffs. Finally, extending the model to allow for lobbying by residents within the downtown retail district we find that residents may lobby for higher or lower parking fees, depending on their relative concern for the vitality of the central district. As a consequence, depending on parameter values, the outcome of lobbying may produce car fees below or above first-best levels. We argue that our results are in line with empirical observations.
Keywords: D72; H23; D43; R41; 330; parking; road pricing; lobbying; retailers; superstores